Assessment of Local Communities' Climate Vulnerability in Lampung: Case Study on Buffering Villages at Way Kambas National Park - Suparjo; F.V. Astrolabe Sian Prasetya; Feri Fadlin; Yulma; Joko Triyono; Nuzula Elfa Rahma; Erna Rositah (Talenta Publisher, 2026)
Communities in Lampung province, Indonesia, are at the forefront of climate change impacts. Hence, this study aims to determine the climatic vulnerability of Lampung local communities. The study encompasses multifaceted aspects of climate exposure and its impact on the local communities of three resorts (Kuala Penet, Susukan Baru, Cabang). The analysis consists of examining historical climate patterns and how they correspond to the community's climate vulnerability. The analysis covers historical climate data from the period of 2004 to 2024, which includes the daily temperature (maximum, minimum, and average value) and daily precipitation. Furthermore, interviews and Focus Group Discsussions are conducted to obtain information from the communities. The data is then interpreted by using the DPSIR framework. It reveals that inland and coastal communities differ regarding these aspects: risk exposure, sensitivity, and adaptive capabilities. When it comes to exposure, inland agricultural communities face risks from drought, soil degradation, and unpredictable rainfall. Meanwhile, coastal communities are affected by rising temperatures, rising sea levels, tidal floods, coastal erosion, and the depletion of fish stocks. Sensitivity is measured by means of livelihood, socioeconomic status, and access to healthcare. Marginalized groups, particularly the poor and elderly, face compounded risks due to limited healthcare access and displacement threats, with the most vulnerable being the coastal communities of Cabang Resort. Furthermore, when it comes to adaptive capabilities, both terrestrial and coastal communities in Lampung have very limited capacities to anticipate most of the climate change impacts. Strengthening climate resilience will require targeted interventions, including improvement of infrastructure, access to healthcare and disaster readiness programs.